Investigating a novel small molecule inhibitor of nuclear import as an anti-cancer approach - Chi, Ru-pin Alicia (Division of Medical Biochemistry, 2017)
The identification of novel cancer-associated biomarkers against which drugs can be developed is anticipated to be beneficial in multiple ways; including their use as monotherapies and in combination with current chemotherapeutic agents for improved anti-cancer treatment outcome. Recently, research in our own laboratory and others have reported elevated expression of the nuclear transporter Kpnβ1 in multiple cancers. Using the cervical cancer model, we showed that its inhibition using small-interfering RNA (siRNA) resulted in cancer cell death via apoptosis while sparing normal cells, suggesting it has potential as a target for anti-cancer therapy. An in silico screen for Kpnβ1 inhibitors identified several small molecules that showed inhibitory effects on nuclear import as well as cancer killing activity. In this study, we aimed to examine the potential of one such small molecule, the Inhibitor of Nuclear Import-43 (INI-43) as a lead compound with anti-cancer activities using multiple cancer models. Through culture-based in vitro assays, we demonstrated that INI-43 inhibited the proliferation of cancer cells grown anchorage-dependently and independently. These effects were similarly observed in Kpnβ1 knock-down cells, and Kpnβ1 over-expression was able to partially reverse these effects, suggesting that the anti-cancer effects of INI-43 is mediated through interference of the Kpnβ1 function. Toxicology studies and liver microsomal assay showed that INI-43 has an acceptable toxicity profile in nude mice and is metabolically stable, allowing its use in in vivo testing. Intraperitoneal administration of INI-43 significantly reduced the growth of subcutaneously xenografted cervical and oesophageal tumour cells in nude mice, supporting its anti-cancer activity in vivo. To examine the potential of using INI-43 in combination therapy, we examined the effects of the combined treatment of INI-43 and Cisplatin (CDDP), a first-line chemotherapeutic agent used in the treatment of many cancers. INI-43 treatment at sub-lethal concentrations enhanced cancer cells' sensitivity to CDDP, which was similarly observed in Kpnβ1 knock-down cells. Using an ovarian cancer model, we demonstrated that CDDP treatment led to elevated expression and nuclear localization of Kpnβ1, suggesting that Kpnβ1 is involved in CDDP-induced stress response. INI-43 treatment impeded the CDDP-induced nuclear accumulation of Kpnβ1 which correlated with increased cell death, suggesting that nuclear localization of Kpnβ1 may be important for ovarian cancer cell survival when challenged with genotoxins such as CDDP. Using the cervical cancer model, we demonstrated that INI-43 enhanced CDDP-induced cell death synergistically, and that the enhanced cell death is mediated through stabilizing p53 protein. This associated with decreased levels of Myeloid Cell Leukemia 1 (Mcl-1), an anti-apoptotic factor negatively regulated by p53. Furthermore, INI-43 treatment reduced the nuclear import of NFκB, a stress-regulated response known to promote cancer cell survival. Decreased levels of various downstream pro-survival and DNA-repair targets of NFκB were observed, including cyclinD1, c-Myc and X-Linked Inhibitor of Apoptosis Protein (XIAP), which correlated with increased DNA damage and apoptosis. Taken together, we show that nuclear import inhibition using small molecules could have therapeutic benefits in the treatment of cancer, and that INI-43 is a promising candidate for further development to be used in anti-cancer monotherapy or combination chemotherapy.